Nursing beliefs and actions in exercising patient advocacy in a hospital context - Jamila Geri Tomaschewski Barlem; Valéria Lerch Lunardi; Edison Luiz Devos Barlem; Aline Marcelino Ramos; Aline Belletti Figueira; Nerizane Cerutti Fornari (SciELO, 2015)
AbstractOBJECTIVEAnalyzing beliefs and actions of nurses in exercising patient advocacy in a hospital context.METHODA quantitative cross-sectional exploratory and descriptive study, conducted with 153 nurses from two hospitals in southern Brazil, one public and one philanthropic, by applying Protective Nursing Advocacy Scale - Brazilian version. Data were analyzed using descriptive statistics and analysis of variance.RESULTSNurses believe they are advocating for patients in their workplaces, and agree that they should advocate, especially when vulnerable patients need their protection. Personal values and professional skills have been identified as major sources of support for the practice of advocacy.CONCLUSIONNurses do not disagree nor agree that advocating for patients in their working environments can bring them negative consequences. It is necessary to recognize how the characteristics of public and private institutions have helped or not helped in exercising patient advocacy by nurses.